Preventive Health Behaviors Pada Caregiver Pasien Lansia Dan Hubungannya Dengan Kepatuhan Pengobatan Di Sulawesi Selatan - Anggriani, A.; Rahmawati, Fita; Wahab, Izyan Abdul (Pengurus Pusat Ikatan Apoteker Indonesia, 2021)
Elderly patients (geriatrics) with various clinical problems arise due to the degenerative process of carrying out personal activities that require assistance from other people called caregivers. A caregiver, in addition to helping with the individual actions of geriatric patients, also plays a full role in the healing process if the patient experiences clinical problems. This can result in caregivers having a mental burden that must be considered so that the care process for elderly patients can run smoothly. This study was conducted to identify aspects of individual caregivers' mastery and examine the method of treating geriatric patients, especially in adherence to medication use. This study used a cross sectional design involving 131 respondents. Data was collected through interviews with caregivers of elderly patients who received health services at the South Sulawesi Health Center. The Pearlin Mastery Score questionnaire instrument was used to measure the mastery of individual caregivers, and the pill counting method was used to determine the level of patient compliance. Data analysis used descriptive statistics and Spearman-rho to determine the relationship between emotional attachment and adherence with geriatric patients. The analysis results showed a correlation coefficient of 0.417**, namely, the level of association between dynamic control variables on the level of compliance of geriatric patients was 0.417 or a moderate correlation with the relationship between variables in the direction and feasible significant (p<0.05). Therefore, to increase the level of satisfaction of geriatrics to meet the needs of geriatrics